Plasma glutamine changes after high-intensity exercise in elite male swimmers - Kargotich, S.; Rowbottom, D. G.; Keast, D.; Goodman, C.; Dawson, B.; Morton, A. R. (Research in Sports Medicine, 2005)
The aim of this study was to establish the pattern and time course of plasma glutamine recovery after acute, high-intensity exercise in well-trained swimmers. In Study 1, elite male swimmers (n = 8) performed 15 × 100m swimming intervals (ITS) at 70% and 95% of maximal 100m freestyle time. Resting plasma glutamine levels were determined on a nonexercise control day (0% ITS). Venous blood samples were obtained prior to, immediately after, and 30, 60, 120, and 150 min postexercise. In Study 2, the 95% ITS was repeated in elite male swimmers (n = 8), while control subjects (n = 8) did not exercise, to test for any diurnal variation in plasma glutamine levels. Venous blood samples were obtained prior to and 2, 4, 6, and 8 h postexercise. In Study 1, no change was observed in plasma glutamine following the 0% (control) and 70% ITS, but following the 95% ITS glutamine decreased significantly (p < 0.01) over the recovery period. In Study 2, plasma glutamine again decreased over the recovery period in the swimmers, but no changes were observed in the controls. It was concluded that intensive swim training results in postexercise decreases in plasma glutamine levels. Because glutamine has been suggested as a marker of overtraining, a need to measure glutamine at standard times within training programs is indicated.